Subwavelength-sized plasmonic structures for high-resolution optical imaging - Wang, Qian (2012)
Optics does not naturally suit the nanometer world because the optical length scale is on the order of several hundred nanometers due to diffraction limit. However, exploiting the hybrid nature of surface plasmons (SPs) offers a way to hurdle this diffraction limit and thus enable a route to subwavelength optics. SPs are essentially light waves coupled to free electron oscillations in a metal, which are strongly confined in the nanoscale region of metal/dielectric interface. The nature of twodimensional evanescent waves bestows SPs the unique capabilities in tailoring optics by subwavelength-sized surface structures to be incorporated into nanoscience for various applications. Specifically, these plasmonic fields hold exceptional promise to miniaturize optical components as well as to provide wide-field view in the field of super-resolution microscopy.The work contained in this thesis is directly towards the design, fabrication and characterization of subwavelength-sized plasmonic structures for integration of the excitation, modulation and interference of SP waves into nanoscale. The subdiffraction SP interference patterns can be served as the excitation profiles in the proposed novel super-resolution fluorescence microscopy.